Peran Modal Sosial Dalam Pengembangan Wisata Berkelanjutan: Studi Kasus di Kawasan Wisata Lumbung Stroberi-Kota Batu - Windiani Windiani; Lienggar Rahadiantino; Eka Dian Savitri; Endang Susilowati (JURNAL SOSIAL HUMANIORA (JSH), 2022)
With Pandanrejo Tourism Village in Bumiaji District, Batu City serving as the focal point of this investigation, the study's overarching objective is to ascertain what part social capital plays in the process of transforming Lumbung Stroberi into a sustainable tourism destination. The concepts of social capital, collaboration, and sustainable development are investigated through the lens of this study, which employs qualitative research methods and a participatory rural appraisal approach to research. Observations of participants and conversations within focus groups are going to be used to collect data. Informants for this study came from local stakeholders who were active in the development of Lumbung Stroberi tourism in Pandanrejo village, which is located in Batu City. The results of this research make a significant contribution to the development of laboratory-based science, in particular the sociology of development. In order to foster more sustainable tourism and community development in Indonesia, local governments and other stakeholders can make use of the practical benefits provided by research.